2014
DOI: 10.1111/spc3.12087
|View full text |Cite
|
Sign up to set email alerts
|

Social Relationships and Health: The Toxic Effects of Perceived Social Isolation

Abstract: Research in social epidemiology suggests that the absence of positive social relationships is a significant risk factor for broad-based morbidity and mortality. The nature of these social relationships and the mechanisms underlying this association are of increasing interest as the population gets older and the health care costs associated with chronic disease escalate in industrialized countries. We review selected evidence on the nature of social relationships and focus on one particular facet of the connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
560
1
43

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 780 publications
(633 citation statements)
references
References 92 publications
29
560
1
43
Order By: Relevance
“…High quality social connections or networks are associated with increased positive health behaviors (Cohen & Janicki-Deverts, 2009;Walton & Cohen, 2011), improved academic outcome (Walton & Cohen, 2011), and reduced depressive symptoms (Williams & Galliher, 2006). Social isolation (SI) is a lack of contact and engagement between oneself and society (Cacioppo & Cacioppo, 2014;Nicholson, 2012;Zavaleta, Samuel, & Mills, 2014). There are two types of social isolation: objective isolation, such as absence or limited number of meaningful social interactions; and subjective isolation where an individual reports feeling socially isolated or loneliness (Cacioppo & Cacioppo, 2014;Zavaleta et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…High quality social connections or networks are associated with increased positive health behaviors (Cohen & Janicki-Deverts, 2009;Walton & Cohen, 2011), improved academic outcome (Walton & Cohen, 2011), and reduced depressive symptoms (Williams & Galliher, 2006). Social isolation (SI) is a lack of contact and engagement between oneself and society (Cacioppo & Cacioppo, 2014;Nicholson, 2012;Zavaleta, Samuel, & Mills, 2014). There are two types of social isolation: objective isolation, such as absence or limited number of meaningful social interactions; and subjective isolation where an individual reports feeling socially isolated or loneliness (Cacioppo & Cacioppo, 2014;Zavaleta et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Perceived social isolation, often described as loneliness, has been referred to as "a chronic distress without redeeming features" (Weiss, 1973, p. 15). Cacioppo and Cacioppo (2014) reported that while loneliness heightened sensitivity to social threats and motivated the renewal of social connections, it also had negative physical health consequences including impaired executive functioning and decreased sleep, mental, and physical well-being. All of these issues may have lasting impacts on the quality of life of both graduates and non-graduates.…”
Section: Reducing Isolation In Students Through New Technologiesmentioning
confidence: 99%
“…As social animals, humans build complex relationships with one another within the community that they live in [1]. Identifying such relationships between patients and their caregivers, family members/dependents, and healthcare providers can help inform community support structures, identify disease discordance/relationship-based clusters, and improve community health care delivery, thus improving the efficiency, effectiveness, and impact of healthcare [2][3][4].…”
Section: Introductionmentioning
confidence: 99%